PENGARUH SIKLUS PENGERINGAN DAN PEMBASAHAN TERHADAP KUAT GESER DAN VOLUME TANAH - Nurdin, Sukiman (MEKTEK, 2010)
Dry and wetting cycle in tropical area are usual cycle with high intensity. Those usually affect soils to beshrinkage at drying condition. It can be determine by the decrease of soil moisture content. In other hand,swelling process will occur in wetting side that actually cause the increase of volume of soils due to watercontent. This phenomena should be can caused by several factors such as soils mineral, climate (intensity ofrain), humidity and gravitation. This study aims to explore the change of volume and shear strength of soilsdue to dry and wetting cycle.Shrinkage limits test shows that shrinkage limit of soils more than 12%, it can be conclude that the typesoils at Kalukubula regency have slightly swelling potential. At 2 days until 10 days in drying process, theshrinkage limit was 21.37% to 47.87% with soil’s volume change from 18.06% decrease to 6.06%. while inwetting process, the shrinkage limit of soils was 46.70% to 26.06% with soil’s volume change from 0.18%increase to 10.17%. Swelling test shows that the swelling potential of soils was lower that 0.5% to average(0.5%- 1.5%). Shear test results in drying condition had the value of cohesion (c) and soil friction angle (ø)higher than in wetting condition